Aggregation state tuning via controlling molecular weights of D–A1–A2 type polymer donors for efficient organic photovoltaics. Issue 13 (9th March 2023) - Wang, Shanlu; Chen, Tianyi; Li, Shuixing; Ye, Lei; Fu, Yuang; Lu, Xinhui; Zhu, Haiming; Zuo, Lijian; Shi, Minmin; Chen, Hongzheng
Abstract : A polymer donor with a D–A1 –A2 type structure was developed, whose aggregation state was tuned by molecular weight control, finally leading to over 15% power conversion efficiency. Abstract : Thiophene ring-based polymer donors generally face the challenges of high-lying energy levels and unfavorable aggregation states, thus limiting the performances of thiophene-based organic photovoltaics (OPVs). Herein, different from the traditional donor–acceptor (D–A) structure, we proposed a novel molecular design strategy of polymer donors by constructing a D–A1 –A2 structure to achieve deep-lying energy levels, yielding PQC-TL, PQC-TM and PQC-TH, whose aggregation states in films could be controlled via molecular weights. A comparable study was performed by pairing these polymer donors with a newly synthesized monochlorinated non-fullerene acceptor L8-Cl. It's found that increasing the molecular weights of polymer donors leads to strengthened aggregation and reduced miscibility between the donor and acceptor, thus manipulating the domain sizes and crystallinity in polymer donor:L8-Cl blend films. An OPV device based on a PQC-TM donor with a medium molecular weight achieves a good balance between high crystallinity for efficient charge transport and suitable domain sizes for least charge recombination, thus enabling the highest efficiency of 15.0%, much higher than those (12.7% and 11.3%) of PQC-TL and PQC-TH-based devices. Anyway, this work demonstrates D–A1 –A2 as a feasible molecular structure for designing efficient thiophene ring-based polymer donors and shows the critical role of molecular weight in controlling the aggregation state and device performance.